Competition for Order Flow as a Coordination Game - Jutta Dönges; Frank Heinemann (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2001)
Competition for order flow can be characterized as a coordination game with multiple equilibria. Analyzing competition between dealer markets and a crossing network, we show that the crossing network is more stable for lower traders' disutilities from unexecuted orders. By introducing private information, we prove existence of a unique equilibrium with market consolidation. Assets with low volatility and large volumes are traded on crossing networks, others on dealer markets. Efficiency requires more assets to be traded on crossing networks. If traders' disutilities differ sufficiently, a unique equilibrium with market fragmentation exists. Low disutility traders use the crossing network while high disutility traders use the dealer market. The crossing network's market share is inefficiently small.
urn:nbn:de:hebis:30-18471
Keywords: 330; Wertpapierhandel; Auftrag; Börse; Elektronisches Handelssystem; E-Business; Wettbewerb; Spieltheorie; Theorie